Obstetric Correlates of Maternal Falls in Southern Nigeria - Jacob Olumuyiwa Awoleke; Babatunde Ajayi Olofinbiyi; Adeola Olabisi Awoleke; Adefunke Christianah Omoyajowo (The Scientific World Journal)
Falls during pregnancy can be associated with serious obstetric complications. Apart from sparse data highlighting traumatic outcomes, there are no studies identifying the obstetric correlates of maternal falls in Nigeria. A cross-sectional cohort survey of 1,175 women in five public health facilities in Ado–Ekiti was conducted to address this need. Fall rate was 25%; mothers who fell during pregnancy were significantly older, of higher parity, and with unintended/unwanted pregnancies than those who did not fall. Most of the reported falls occurred in the third trimester, with about 10% of the women falling at least thrice during the course of the pregnancy. More than half of the reported falls occurred while engaging in household chores and carrying child/object with compromised visibility of the feet and floor. Uterine contractions/abdominal pain was the commonest; 29 (76.3%), obstetric event attributed to the falls. Antepartum haemorrhage, 4 (10.5%), and ruptured membranes, 2 (5.3%), also occurred after falls, although it was rare and occurred with the same frequency as in the general population. Maternal age ≥ 30 years (odds ratio: 1.36; 95% C.I. 1.03 – 1.80, p = 0.031), multiparity (odds ratio: 1.54; 95% C.I. 1.15 – 2.07, p = 0.004), unintended pregnancy (odds ratio: 1.48; 95% C.I. 1.02 – 2.15, p = 0.037), and delivery age ≤ 40 weeks (odds ratio: 1.71; 95% C.I. 1.07 – 2.75, p = 0.026) were found to be independent risk factors for falls during pregnancy. Fall awareness campaigns and fall-preventing safety tips are advocated in women’s clinics. Improving contraceptive uptake will reduce unintended pregnancies and the risk of pregnancy-related fall/injuries.